Malocclusion prevalence and orthodontic treatment need in central Anatolian adolescents compared to European and other nations' adolescents - Bilgic,Fundagul (2015)
Abstract Objective: To determine the prevalence of malocclusion and orthodontic treatment need in a large sample of Central Anatolian adolescents and compare them with European-other nations' adolescents. Methods: The sample included 1125 boys and 1204 girls aged between 12 and 16 years with no previous orthodontic treatment history. Occlusal variables examined were molar relationship, overjet, overbite, crowding, midline diastema, posterior crossbite, and scissors bite. The dental health (DHC) and aesthetic components (AC) of the Index of Orthodontic Treatment Need (IOTN) were used as an assessment measure of the need for orthodontic treatment for the total sample. Results: The results indicated a high prevalence of Class I (34.9%) and Class II, Division 1 malocclusions (40.0%). Moreover, increased (18%) and reduced bites (14.%), and increased (25.1%) and reversed overjet (10.%) were present in the sample. Conclusion: Using the DHC of the IOTN, the proportion of subjects estimated to have great and very great treatment need (grades 4 and 5) was 28.%. However, only 16.7% of individuals were in need (grades 8-10) of orthodontic treatment according to the AC.